Studies in Targum Isaiah : Textual Witnesses, Translation Techniques, and Theological Explorations - Houtman, Alberdina, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Studies in Targum Isaiah: Textual Witnesses, Translation Techniques, and Theological Explorations is the culmination of 30 years of in-depth research into Targum studies. This comprehensive work offers a detailed description and comparison of available manuscripts, an analysis of translation techniques, and essays exploring the theological perspectives of the translators. The final chapter delves into the risks and opportunities of intertextual comparison with the New Testament, providing a thoughtful perspective for scholars and students alike. Essential for anyone interested in biblical studies, this book offers valuable insights into the complexities of Targum Isaiah and its relevance in theological discourse.